Chartering and Financial performance in Shipping - Kouspos, Andreas (My University, 2022)
This dissertation includes essays in the topic of chartering, technical innovation in shipping, risk and return in shipping and shipping financial performance. Chapter 1 investigates the relationship between chartering policy and financial performance of U.S. listed shipping firms using publicly available data from SEC’s 20-F forms for U.S. listed shipping firms to construct a unique dataset of vessel chartering decisions. Also, firm-level data is used during the econometric modelling of panel data which are employed as a methodology for investigating this research gap. Results show that employing a long-term chartering strategy i.e., time charter with duration more than a year, shipping firms can achieve higher financial performance for the sample’s period which is characterized as ‘bearish’. The higher the deadweight tonnage chartered under time charter with duration more than 1 year, the higher the financial performance of shipping firms. Also, chartering capabilities are important for the shipping firm for making the best decision for chartering its ships as efficiently as possible at the right time. After the shipping crisis of May 2008, it seems that shipowners prefer to follow the path of safety by chartering their most of ships under long-term chartering contracts. Results are of interest to shipowners and ship lending authorities, mostly for improving financial performance and ensuring that loan settlement are being paid respectively. Chapter 2 reviews the relationship between ship’s technical innovation of U.S. & Oslo listed shipping firms with financial performance. Annual data for technical innovation for 21 shipping firms from 2013 to 2019 is collected from SEC 20F forms from Securities and exchange commission (Edgar) for U.S. listed shipping firms and firms’ webpages for Oslo listed shipping firms. Data for technical innovation includes eco-type ship, ship’s propulsion type and ice class type ships. Panel data regression modelling is applied showing that technically innovated ships have a positive robust relationship with shipping firms’ financial performance. In line with the academic literature, innovation contributes to higher financial value for a firm. Among the three types of technical innovation, eco-type contributes to higher financial performance of shipping firms. This can be seen as an attempt of shipping firms to embrace corporate social responsibility (CSR) techniques which is positively seen by shipping investors in the market. Going ‘green’ can positively affect firm’s financial performance because shipping investors seems to embrace these green practices. Chapter 3 examines the relationship between chartering policy and financial performance of U.S. listed shipping firms trading in the dry bulk and tanker shipping segments of the industry. We collect data for dry and tanker firms listed in U.S. stock exchanges, NYSE and NASDAQ from SEC 20F forms from the Securities and exchange commission (Edgar). These sub-segments in the shipping market have different business cycles which are formed by the demand and supply for transporting various commodity types worldwide. Panel data regression modelling is applied resulting that chartering policy in both segments differs and as a result there is a different impact on the financial performance for each shipping segment. We also compute volatilities/risks of freight rates for spot and time charter markets for assessing uncertainty in each market. Results show that employing a higher percentage of ships under time chartering strategy with duration more than a year in the dry segment has a higher impact on financial performance compared to tanker shipping segment. In contrast, employing a higher percentage of the fleet in the spot market in the tanker shipping segment compared to dry segment has a higher impact on shipping firms’ financial performance. Results are useful for the risk averse investors who can diversify risks by investing in dry bulk shipping firms trading most of their fleet under time chartering and in tanker shipping firms employing most of their fleet under voyage charter.
Keywords: Shipping chartering; Financial performance